THE INFLUENCE OF USING INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) TOWARDS TEACHERS’ PERFORMANCE IN SMA NEGERI 1 CIAWI TASIKMALAYA - Erna Rusmiwati Sukandar; Endang Syarif; Maharani Amatilah Putri (Perwira Journal of Economics & Business, 2021)
This research was conducted based on the problems of using Information and Communication Technology (ICT) towards teachers’ performance in SMA Negeri 1 Ciawi Tasikmalaya. Due to the lack of expertise in using ITC, and the use of foreign languages that did not understand that system, so the teachers should have to carry out training, perseverance and discipline by using that ICT. The aim of the research is to determine how to due the application of information and communication technology can be impact to the teacher’s performance with the use of application of ICT in SMA Negeri 1 Ciawi. This research used descriptive quantitative method. The population of this study were 68 teachers in SMA Negeri 1 Ciawi. The sample was selected by using saturated sample method. The instrument of this research were taken interview, observation and questionnaire. The research instrument was tested by means of validity and reliability test. The results of this study indicated that the application of Information and Communication Technology (ICT) in SMA Negeri 1 Ciawi is in poor classification, teachers’ performance in SMA Negeri 1 Ciawi is in good classification, and there is a significant relationship between the Application of ICT to Teachers’ Performance in SMA 1 Ciawi.